A flexible approach for the dimensioning of on-site energy conversion systems for manufacturing companies. (September 2021) - Gahm, Christian; Ganschinietz, Chantal; Denz, Florian; Tuma, Axel
Highlights: Design of on-site energy conversion systems (ECS) notably effects energy efficiency. Interdependencies between production, ECS operation, and ECS design are anticipated. Nonlinear part-load efficiencies are explicitly considered and analyzed. For solving, a heuristic and mixed-integer non-linear program are presented. The evaluation shows the influences of ECS parameters and scheduling objectives. Abstract: Besides electricity, many industrial production processes require other energy sources such as steam or pressure. To transform primary or secondary energy sources into the required energy sources, manufacturing companies often operate their own on-site energy conversion system. Most important parameters determining a conversion systems' overall degree of efficiency are the dimension of its conversion units (CUs) and the design point (nominal load) at which a CU operates with maximum efficiency. In addition, conversion efficiencies at part load are particularly important because strongly varying energy demands from production processes frequently forcing an operation different from the nominal load. The (mostly) nonlinear relationship between part load operation and conversion efficiency makes an adequate consideration of this relationship essential. To address these factors, we present a new conversion system design approach aligned for manufacturing companies. To maximize energy efficiency, we propose a heuristic and a mixed-integer nonlinear program. In the experimental analysis, we analyze different types of companies, several CU parameter settings, the influence of nonlinear and linear efficiency modelling, and the influence of different machine scheduling objectives on the conversion system design. The results show that all these factors can remarkably influence the design and the energy efficiency of a conversion system.